The impact of service promotion on achieving leadership for business organizations - الجعفري اشراق محسن; محمد عالية جواد (Journal of Economics and Administrative Sciences, 2020)
The research problem lies in the fundamental questions that revolve around the role of each of the tools of promotion, namely advertising, personal sale, public relations, sales promotion, and direct marketing in achieving leadership for business organizations. Research to know the role of promoting the service in the researched company and whether the promotion of the service is qualified to lead the researched company to leadership, and for this purpose formulated research hypotheses of three hypotheses, the first hypothesis says that there is a significant impact relationship between promotion and entrepreneurship. The second hypothesis aimed to determine the role played by promotion in the researched company to achieve uniqueness and excellence over its competitors, while the third main hypothesis was that (There is an impact of the dimensions of the promotion combined in entrepreneurship). To test the hypotheses of the research was applied research in the Iraqi Airways Company, where the sample of the research (75) managers of senior and middle management leaders in the company. Data were collected using the questionnaire and personal observations by using (SPSS-v24) program and a set of statistical methods. One of the most important conclusions of the research is that the airline takes into account the promotion of the service to an acceptable degree, which enhances the possibility of promotion in making the company abler to achieve leadership and dominance and superiority over target markets. The conclusion of the research was a set of recommendations, most notably the importance of the attention of Iraqi Airways to develop and activate new and innovative means of promotion, as well as the use of technologies that are broader and more comprehensive to be able to reach the public.